Pelaksanaan Program Peningkatan Mutu Pendidikan di Madrasah Padang Lawas Kecamatan Barumun Tengah - Hasibuan, Alwi Hamdani; Syafaruddin, Syafaruddin; Tanjung, Zulkifli (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
This study aims to describe (1) the implementation of the Education Quality Improvement Program at MAN 2 Padang Lawas, Barumun Tengah District; (2) supporting and inhibiting factors in the implementation of the program. This research is a qualitative descriptive study. This research was conducted at MAN 2 Padang Lawas, Barumun Tengah Subdistrict in October-November 2021. The research subjects were principals, vice principals, teachers, and students. Data was collected by observation, interviews, and documentation. The data were analyzed interactively by the Miles and Hubberman model, namely data reduction, data presentation, and drawing conclusions. The validity of the data was tested by triangulation. The results showed that (1) the implementation of the Education Quality Improvement Program at MAN 2 Padang Lawas, Barumun Tengah District had been carried out by a) routine internal and external communication through meetings, d) a good commitment from the implementor as well as a high concern and democratic climate from the leader during policy implementation, c) the school's vision and mission as the basis for development and development of school culture, d) good and innovative managerial activities; (2) supporting factors for implementing the policy are qualified, multitalented, and highly educated educators and education staff. On the other hand, the inhibiting factors are a) the low quality of the input (students) and b) the unfinished school construction program.